2016
DOI: 10.1007/s10972-016-9470-7
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Reform-Oriented Secondary Science Teaching Through the Use of a Framework to Analyze Construction of Scientific Explanations

Abstract: The Next-Generation Science Standards (NGSS) call for a different approach to learning science. They promote three-dimensional (3D) learning that blends disciplinary core ideas, crosscutting concepts and scientific practices. In this study, we examined explanations constructed by secondary science teacher candidates (TCs) as a scientific practice outlined in the NGSS necessary for supporting students' learning of science in this 3D way. We examined TCs' ability to give explanations that include explicit statem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…An example of an article that did make the CCCs explicit to students is Leckie and Wall (2017), who described how one teacher made the connections between CE explicit to students in their academic writing. Some articles did describe explicitly supporting preservice (e.g., Richmond et al, 2016) or in‐service teachers (e.g., Criswell et al, 2018; Roseman et al, 2017) with using the CCCs. However, the articles often did not describe how these same concepts would be made explicit to their students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of an article that did make the CCCs explicit to students is Leckie and Wall (2017), who described how one teacher made the connections between CE explicit to students in their academic writing. Some articles did describe explicitly supporting preservice (e.g., Richmond et al, 2016) or in‐service teachers (e.g., Criswell et al, 2018; Roseman et al, 2017) with using the CCCs. However, the articles often did not describe how these same concepts would be made explicit to their students.…”
Section: Resultsmentioning
confidence: 99%
“…Through analyses of performance tasks, Peters and Songer (2013) found that students' difficulties with the CCC of SPQ created struggles in their ability to use technology to model climate change, suggesting that the CCCs were an important place to develop scaffolding. In their work with a science methods course, Richmond et al (2016) found that many preservice teachers, regardless of major, struggled to provide causal explanations of science concepts. These researchers found relationships between struggles with the CCCs and a lack of depth in content understanding or learning.…”
Section: Theme 3: Connected To Big Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…American science education has been criticized for focusing on transmission of scientific facts and implementation of "cookbook" labs (Osborn, 2014;Richmond, Parker, & Kaldaras, 2016). With the inception of the Next Generation Science Standards (NGSS Lead States, 2013), reform initiatives seek to move American, science education away from final-form science and toward engaging students in scientific practice.…”
Section: Introductionmentioning
confidence: 99%
“…The third paper, presented by Richmond et al (2016), was concerned with supporting reform-based secondary science teaching. In particular, this support was in the form of developing and using a framework for analyzing the construction of scientific explanations.…”
mentioning
confidence: 99%